ChemInform Abstract: Structure and Reactivity of Indolylmethylium Ions: Scope and Limitations in Synthetic Applications. Issue 4 (January 2016) - Follet, Elsa; Berionni, Guillaume; Mayer, Peter; Mayr, Herbert
Abstract: The reactivity of the title compounds with π‐nucleophiles (silylated enol ethers and ketone acetals) is kinetically studied using photometric monitoring at 20°C.